The Economic Impacts of Aging Societies - Alper, Findik Ozlem; Alper, Ali Eren; Ucan, Okyay (International Journal of Economics and Financial Issues, 2016)
Changes occuring in the health sector and in terms of society within the last 100 years in the world has extended the life expectations at the time of birth and decreased the birth rates. These changes have been experienced especially in developed countries rather than the underdeveloped and developing countries. The aim of this study is to make the determination of the economic effects of growth by using panel data analysis method for 2000-2014 period in 19 developed countries consisting of USA, Canada, England, Germany, France, Japan, Belgium, Australia, Luxembourg, Switzerland and Denmark. The panel corrected Standard errors (PCSE) regression test results show that the income per capita is directly proportional with the income per worker and labour force total participation rate (LFTP). So when the average of age increases LFTP decreases and this affects negatively the national income of countries. Keywords: Aging; Labour Force Participation Rate; Panel Data Analysis JEL Classifications: J11; J21; C23